Bicoastal Spontaneous Coronary Artery Dissection: A Therapeutic Dilemma - Nguyen Pham, Ann B.; De Zoysa, Madushka Y.; Ghoshhajra, Brian B.; Scott, Nandita S.; Hameed, Afshan B. (American Journal of Perinatology Reports, 2024)
Due to the potential for severe maternal morbidity and even mortality, pregnancy-associated spontaneous coronary artery dissection (P-SCAD) often presents as a clinical conundrum. While current recommendations encourage coronary interventions when medically indicated even during pregnancy, the hesitation still understandably exists. Meanwhile, given the rarity of the condition, the guidelines for management are still based on expert consensus.We present a case of P-SCAD in a 38-year-old woman with initial presentation at 28 weeks' gestation and recurrence at 9 days postpartum. A unique complication of this case is its transcontinental nature: the initial event occurred while the patient was on vacation across the country from her home. Questions arose not only with regard to her immediate management and care but also when she would be able to travel and how her complex care would be continued cross-country.This case raised important questions regarding the antepartum management of acute coronary syndrome (ACS). It also highlights the importance of multidisciplinary care, especially with a cardio-obstetrics team, in the management of P-SCAD and emphasizes the role for universal screening for cardiac diseases in pregnancy.
Keywords: Keywords; pregnancy; spontaneous coronary artery dissection; pregnancy-associated SCAD